DRAWING IN THE SYSTEM OF ARTISTIC AND PEDAGOGICAL TRAINING OF STUDENTS - Nuriddinova Mohigul (Zeta Repository, 2023)
The article describes the problem of teaching drawing to students of a pedagogical institute. the article considers various types of educational and creative drawings, classroom and extracurricular forms of pictorial activity. It also describes traditional and innovative drawing classes, including academic drawing from nature, illustration works and art activities in natural settings. Plein air is described as a source of authentic artistic images and an effective means of teaching painting to future teachers. The material of the article can be useful for higher art-pedagogical education of students, methods of teaching visual arts and teachers.